Psychological consequences of unemployment: moderating role of education - Galić, Zvonimir (Array, 2007)
The study aims to examine whether unemployed individuals with different educational levels experience equally severe psychological consequences of unemployment and whether these consequences are differently related to the two theoretical predictors (psychological and financial deprivation). The data were collected in 26 branch offices of the Croatian Employment Bureau, on a representative sample of the unemployed persons in Croatia. In order to examine the moderating role of education, participants were divided into the following three subgroups: primary school (N1=174), high school (N2=762) and university degree (N3=196). The unemployed with lower education reported a lower level of psychological health than individuals with higher education. In addition, it was confirmed that educational level has a moderating role on the relationship between psychological deprivation and psychological health